Phosphorylation Modulates Ameloblastin Self-assembly and Ca2+ Binding - Stakkestad, Øystein; Lyngstadaas, Ståle P.; Thiede, Bernd; Vondrasek, Jiri; Skålhegg, Bjørn S.; Reseland, Janne E. (Frontiers in Physiology, 2017)
ABSTRACT Ameloblastin (AMBN), an important component of the self-assembled enamel extra cellular matrix, contains several in silico predicted phosphorylation sites. However, to what extent these sites actually are phosphorylated and the possible effects of such posttranslational modifications are still largely unknown. Here we report on in vitro experiments aimed at investigating what sites in AMBN are phosphorylated by casein kinase 2 (CK2) and protein kinase A (PKA) and the impact such phosphorylation has on self-assembly and calcium binding. All predicted sites in AMBN can be phosphorylated by CK2 and/or PKA. The experiments show that phosphorylation, especially in the exon 5 derived part of the molecule, is inversely correlated with AMBN self-assembly. These results support earlier findings suggesting that AMBN self-assembly is mostly dependent on the exon 5 encoded region of the AMBN gene. Phosphorylation was significantly more efficient when the AMBN molecules were in solution and not present as supramolecular assemblies, suggesting that posttranslational modification of AMBN must take place before the enamel matrix molecules self-assemble inside the ameloblast cell. Moreover, phosphorylation of exon 5, and the consequent reduction in self-assembly, seem to reduce the calcium binding capacity of AMBN suggesting that posttranslational modification of AMBN also can be involved in control of free Ca2+ during enamel extra cellular matrix biomineralization. Finally, it is speculated that phosphorylation can provide a functional crossroad for AMBN either to be phosphorylated and act as monomeric signal molecule during early odontogenesis and bone formation, or escape phosphorylation to be subsequently secreted as supramolecular assemblies that partake in enamel matrix structure and mineralization.